Rebel Cinderella : from rags to riches to radical, the epic journey of Rose Pastor Stokes - Hochschild, Adam (Houghton Mifflin Harcourt, 2020)
"From the bestselling author of King Leopold's Ghost and Spain in Our Hearts comes the astonishing but forgotten story of an immigrant sweatshop worker who married an heir to a great American fortune and became one of the most charismatic radical leaders of her time"--